Ibm Smk Muhammadiyah Sumoroto Pelatihan Pembuatan Film Animas - Dyah Mustikasari (Universitas Muhammadiyah Ponorogo, 2017)
Sekolah Menengah Kejuruan (vocational school) has a purpose to generate graduate which is ready to be employed. Therefore, the students need to have additional competence. It will be additional value for students to compete in the workplace environment. SMK Muhammadiyah Sumoroto is one of vocational schools in Kecamatan Kauman, Kabupaten Ponorogo. This school has two majors; there are accounting and computer networking technique. To improve students’ skill and creativity in graphic design needs to carry out training in Graphic Design, particularly animation design. This training is carried out in SMK Muhammadiyah 1 Sumoroto with participants as many as 20 students from first and second grade. The software used in this training was Alice3 because it is pretty easy to run for beginners in animation design. The training was conducted twice and additional meeting to review and to discuss the result. The biggest obstacle of this training is a lack of computers. The amount of computer was less adequate, so that one computer was used by more than one student. It lead the training become less maximum. Overall the students could have used the software though the result have not been perfect yet.